Edukasi Pemanfaatan Taman Obat Keluarga Untuk Meningkatkan Imunitas Tubuh - Nugraha, Dimas Pramita; Afdal, Afdal (FKM UIN Sumatera Utara Medan, 2023)
An unsanitary environment and living behavior causes humans today to be vulnerable to the threat of disease agents such as bacteria, fungi and viruses. Therefore, efforts to maintain our immune system so we don't get sick easily become very important.The purpose of this community service is to increase public knowledge about the use of family medicine gardens to increase body immunity, especially during this COVID-19 pandemic. The location of this service is in Sialang Kubang Village, Perhentian Raja District, Kampar Regency.This service method is carried out by providing public education through counseling, posters and handouts about the use of family medicine gardens (TOGA) to increase body immunity. Evaluation of community knowledge is carried out by looking at the results of the pretest and posttest before and after the provision of education. The results of the pretest describe the proportion of people who have good knowledge of 18.18% and after the post-test it increases to 63.64%, people who are given education show increased knowledge about the use of TOGA to increase body immunity.